Raising effectiveness of access control systems by applying multi-criteria decision analysis: part 1 – problem definition - Marozas, Leonardas; Goranin, Nikolaj; Cenys, Antanas; Radvilavičius, Lukas; Turskis, Zenonas (Technological and Economic Development of Economy, 2013)
Currently, control of access to information and physical resources has become extremely important. Numerous methods and solutions for architecture of systems aimed at controlling physical access are available; however, there is little information about application of Multi-Criteria Decision Analysis methods when evaluating separate logical components, needed for the design of access control systems and their interconnection in the final architecture.This paper is the first part of a two-part article, discussing application of multi-criteria decision making for architecture of access control systems. The first part defines the problem and discusses the possibility to use Multi Criteria Decision Making techniques when designing access control systems, including risk analysis for specific criteria and practical application of the developed model. In the second part, the possible solution model will be presented.